Impacts of Economic and Programmatic Changes on Medicaid Enrollments - Cromwell, Jerry; Hurdle, Sylvia; Wedig, Gerard (The Review of Economics and Statistics, 1986)
A bstractNewly collected data from the Health Care Financing Administration are utilized to construct an unprecedented quarterly series on Medicaid enrollments to study the economic and institutional determinants of program size. The results suggest that while increased unemployment added nearly one million people to the rolls during an eighteen month interval between 1981 and 1982, net enrollments actually fell by 6.6% over this period mostly because Reagan-sponsored legislation tightening eligibility requirements disenrolled approximately 2 million people. The methodology employed is a first difference regression specification utilizing a GLS correction for serial correlation.